Harmonic-emission from Rydberg states in the vicinity of metallic nanostructures - YAVUZ, İLHAN; ALTUN, ZİKRİ (IOP PUBLISHING LTD, 2015)
We theoretically demonstrate that harmonic emission could be achieved from Rydberg atoms without deteriorating the nanostructures.